The Impact of Financial Literacy, Risk Tolerance, and Overconfidence on Investment Understanding in the Capital Market - Ari, Muhamad As; Susandra, Farizka; Anwar, Saeful (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the influence of financial literacy, risk tolerance, and overconfidence on investment understanding in the capital market. In this research, the method used is quantitative with an associative problem formulation, with a sample of 100 respondents determined using a purposive sampling technique. The results of this study indicate that the t-statistic value for the financial literacy variable is 2.584 > 1.989 and the p-values value is 0.012 < 0.05. Risk tolerance has a t-statistic value of 3.301 > 1.989 and a p-values value of 0.001 < 0.05, while the overconfidence variable has a t-statistic value of 0.541 < 1.989 and a p-values value of 0.590 > 0.05. It can be concluded that financial literacy and risk tolerance have a positive and significant effect on investment understanding in the capital market. The overconfidence variable has no effect on investment understanding in the capital market. The risk tolerance variable is the most dominant in influencing investment understanding in the capital market, so the higher a person's risk tolerance, the higher their investment understanding. The novelty of this research lies in the measurement of the dependent variable investment understanding. The use of this variable provides a new perspective in understanding the factors that influence individual investment behavior in the investment world.